Pemberdayaan Pertanian Terpadu Bermodal Limbah Ladang, Dapur dan Kandang Berbasis Koperasi di Desa Cibitung Tengah, Bogor - Dimas Andrianto; Husnawati; Zulfikar Muchammad; Danty Oktiana Prastiwi; Gina Oktaviani Sabrina; Muhammad Farhan; Imelia Dewi; Elgiani Yassifa Yulia Nur Insari; Amrista Fanzani Kananga; Slamet Hamzah; Sri Wahyuni; Muhammad Irfansyah Pradika (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Farming in Cibitung Tengah Village, Tenjolaya Subdistrict, Bogor District, West Jawa is characterized by vegetables and sheep farming. Several problems in farming are the use of chemical fertilizers, management of agriculture and domestic wastes properly; even some people disposing of garbage in the river and also, the institutional Farmer Group Association (Gapoktan) and Female Farmer Group (KWT) are not functioning optimally. The use of an integrated farming system can increase land and livestock productivities and reduce the volume of agriculture and domestic wastes all at once. This community empowerment activity aimed to increase the people's knowledge and skill of Cibitung Tengah Village in terms of processing agricultural and domestic wastes. Thus it will overcome the garbage and overuse of chemical fertilizer problems. The discussions and outreach activities were done by a door-to-door approach, especially for people who have not been actively involved in Gapoktan and KWT. This research was carried out with several educational activities such as counseling on community waste management systems, training on organic waste processing, Black Soldier Fly (BSF) training, processing organic waste with BSF technology, making silage as goat feed, and making branding of agricultural products. This empowerment program produced new products or processed products. The products will increase the income for the people of Cibitung Tengah, such as maggot processing products, CS-Fresh products, results from waste banks, and handicraft products from waste.